2017
DOI: 10.3390/ma10010038
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Properties of the Mixed n-Octadecane/Cu Nanoparticle Nanofluids during Phase Transition: A Molecular Dynamics Study

Abstract: Paraffin based nanofluids are widely used as thermal energy storage materials and hold many applications in the energy industry. In this work, equilibrium and nonequilibrium molecular dynamics simulations are employed to study the thermal properties of the mixed nanofluids of n-octadecane and Cu nanoparticles during phase transition. Four different nanofluids systems with different mass ratios between the n-octadecane and Cu nanoparticles have been studied and the results show that Cu nanoparticles can improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Further, excess heat is released by the MOHCs during the condensation process as a consequence of the exothermic adsorption of refrigerant molecules into MOF particles. Additionally, the thermal conductivity of the working fluid is enhanced by adding nanoparticles [ 4 ]. The reported research works [ 5 , 6 ] indicated that the enhancement of the thermal properties of nanofluid are mainly due to the effective medium theory.…”
Section: Introductionmentioning
confidence: 99%
“…Further, excess heat is released by the MOHCs during the condensation process as a consequence of the exothermic adsorption of refrigerant molecules into MOF particles. Additionally, the thermal conductivity of the working fluid is enhanced by adding nanoparticles [ 4 ]. The reported research works [ 5 , 6 ] indicated that the enhancement of the thermal properties of nanofluid are mainly due to the effective medium theory.…”
Section: Introductionmentioning
confidence: 99%
“…Dispersing nanoparticles into traditional working fluids, e.g., water, alcohol, oil, and refrigerants, to produce uniform and stable nanofluids can effectively improve the thermal conductivity of working fluids [ 3 , 4 , 5 , 6 ]. Nanofluids have great prospects for application in the fields of energy, chemical engineering, automobiles, building and construction, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the thermophysical data of R1234ze was retrieved via NIST. UIO-66 is a new type of material; the internal energy changes of the UIO-66 structure with temperature can be obtained by molecular dynamics (MD) simulations [24,25]. The desorption heat of R1234ze in UIO-66 is calculated by grand canonical Monte Carlo (GCMC) simulations [26,27].…”
Section: Simulation Methodsmentioning
confidence: 99%